Critical properties of acoustic wave absorption in the benzonitrile-isooctane system - HORNOWSKI, T.; ŁABOWSKI, M. (Archives of Acoustics, 1996)
Experimental results for the absorption of ultrasonic waves in critical benzonitrile + isooctane mixtures in the frequency range 5–21 MHz and at temperatures 0.15 ≤ T – Tc ≤ 20 K are reported and confronted with the Shiwa-Kawasaki's mode-coupling theory. The theoreticalscaling function was found to describe the experimental results correctly throughout the reduced frequency range ω* < 50. The values of certain thermodynamic parameters necessary for the determination of the reduced amplitude A(ε) were calculated using the linear relation between αc/f2 and f-1.06 predicted by the Bhattacharjee-Ferell dynamic scaling theory.